Bill patterns of the Whooper Swan in Finland during autumn migration - Ohtonen, Arvo (Wildfowl, 1988)
Bill patterns of Whooper Swans in Finland differ from those observed in Great Britain and Japan, the proportion of yellow being higher than in Britain and lower than in Japan. This supports the idea of a geographical cline in bill patterns of this species in which the proportion of yellow increases from west to east.